ANALISIS KINERJA GURU PENDIDIKAN JASMANI DALAM PEMBELAJARAN SECARA DARING SELAMA MASA PANDEMI COVID-19 - Mochamad Ginanjar, - (2022)
Entering the new normal era, a number of schools implemented an online learning system or better known as an online learning system (on the network) including Physical Education learning. Physical education learning, which is closely related to face-to-face physical activity, has now turned into learning that is carried out remotely due to the Covid-19 pandemic. The purpose of this researcher is to determine the performance of physical education teachers in online learning during the Covid-19 pandemic referring to teacher competencies, learning processes, and learning evaluations. The method of this research is to use a mixed method with a covergent design. The instruments used are questionnaires and interviews. The population in this study were 8 physical education teachers at the SMKN level in Serang City with a total sampling approach. The findings of this study quantitatively the competence of physical education teachers at the State Vocational School in Serang City has a value of 322.5 with a good category, the physical education learning process at the State Vocational School in Serang City has a value of 57.75 with a good category, and evaluation of physical education learning at the State Vocational School in the City Serang has a value of 65.63 with a good category. Qualitative research findings show that teachers have good competencies, processes, and evaluations of learning. The conclusions in this study refer to teacher competencies, learning processes, and learning evaluations, so physical education teachers at the State Vocational School in Serang City in online learning during the covid pandemic have good performance. Keywords: Teacher Performance, Teacher Competence, Process, Evaluation, Online Learning, Physical Education, Covid-19